Factors Associated with Pre-Hospital Clinical Improvement in Non-Trauma Emergencies: A Cross-Sectional Analysis - Zulmah Astuti; Okdwi Ganda Arianto; Maridi M Dirdjo (Yayasan Ahmad Mansyur Nasirah, 2026)
Ambulance response time is a key performance indicator of Emergency Medical Services (EMS) and is essential for early patient stabilization. However, evidence on factors associated with pre-hospital clinical improvement, particularly changes in the Australasian Triage Scale (ATS), remains limited in developing countries. This study aimed to identify factors associated with pre-hospital clinical improvement among non-trauma emergency patients. A cross-sectional analytical study was conducted involving 113 non-trauma emergency patients transported by ambulance to a tertiary referral hospital in Samarinda, East Kalimantan, Indonesia. ATS improvement was defined as a positive shift to a lower-acuity category between the initial assessment at the emergency scene and reassessment at the emergency department. Data were analyzed using multivariate logistic regression controlling for age, transport distance, diagnosis, and pre-hospital interventions. Ambulance response time of ≤15 minutes was the strongest factor associated with ATS improvement (p < 0.001; adjusted OR = 0.019; 95% CI = 0.003–0.122). Circulation management during pre-hospital care also significantly improved clinical status (p = 0.039), whereas age (p = 0.298) and transport distance (p = 0.114) showed no significant association. These findings indicate that rapid ambulance response and appropriate pre-hospital interventions are strongly associated with improved clinical outcomes in non-trauma emergencies. Although the cross-sectional, single-center design limits causal inference and generalizability, strengthening EMS dispatch systems and timely pre-hospital care remains essential for optimizing patient outcomes.